Application of Artificial Intelligence-Based Computation in the Health Sciences to Ward off the COVID-19 Pandemic - Parikesit, Arli Aditya; Ratnasari, Nanda Rizqia Pradana; Anurogo, Dito (International Journal of Human and Health Sciences (IJHHS), 2020)
COVID-19 pandemic is not slowing down, while the government from various countries is currently designing the ‘new normal’ to restart back their economy. Up to now, there is a significant mortality rate in the health care professionals that act as the frontliners in the hospitals and clinics in battling the COVID-19 menace. Based on computational sciences studied since the 1960s, artificial intelligence (AI) could assist healthcare professionals to protect themselves from the SARS-CoV-2 virus and treat the patients in an efficient and secure manner. AI, starting from the diagnosis, treatment, medication, until the prediction of the next pandemic, could assist in various areas. The objective of this review is to highlight AI in the health sciences in order to assist healthcare professionals in facing the COVID-19 pandemic, and the threat of the future pandemics. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 177-184